A comparative analysis of the right to access to environmental information in South Africa and Uganda. Issue 3 (2nd September 2017) - Ashukem, Jean-Claude N.
Abstract: Even though the Ugandan legal framework on the right to access to environmental information has been described as one of the best in East Africa, it raises some legal concerns that could conceivably result in the limitation of the effectiveness of the right to access to information in the country. For example, the legal framework obliges only public bodies and not also private bodies to disclose vital information to the public. Also, there is great inconsistency between the constitutional and legislative limits of the right. The aim of this article is to critically appraise the Ugandan legal framework on the right to access to environmental information to determine whether the existing legal concerns constitute serious legal flaws, and if so, if this could greatly hinder the public right to gain access to vital information. During the course of this appraisal, the article compares the Ugandan legal regime with the South African equivalent, because the right to access to information is firmly entrenched in the South African legal framework and has been fleshed out to a considerable extent by the South African courts. Using the South African legal framework as a model could thus help to provide a comprehensive and workable solution to some of the legal challenges experienced by Uganda. The article concludes that there is a need for the Ugandan legislature to draw from the South African experience in order to address the existing concerns about the right to access to information in the country.